Cuff pressure management and VAP: Malaysian nurses’ perspective - Mohd Ali, Noor Azizah (2016)
Management of cuff pressure is a pivotal element in a caring for intubated patients in critical care settings. The role is fundamental for nurses and respiratory therapist to the prevention of oropharyngeal and/ gastric secretions aspiration and tracheal damage, in which predispose to VAP. The variation of practices may subject to countries and individual settings’ policies. These are based on evidence published in numerous research articles. Malaysia is a developing country that also acknowledges the importance of the prevention of VAP and places a full commitment and consistent surveillance with the aim to reduce the incidence of VAP. Most of the Malaysian hospitals are using cuff pressure measurement (CPM) and at per shift basis and interestingly, it is included in ventilator care bundle. The crucial time will be post- intubation and upon arrival to ICU. The range is between 25 -30cmH20 and documented in ICU chart. Nevertheless, with the experience of our nurses in clinical practice, the range maybe slightly difference based on the individual patient’s condition. Nurses are empowered to be the one whom responsible to inflate and deflate the cuff wherever needed. Reliable submission of VAP surveillance in hospitals centred in the national database allowing close monitoring the incidence of VAP.